Dalbergia ecastaphyllum leaf extracts: in vitro inhibitory against enzymes related to metabolic syndrome, inflammation and neurodegenerative diseases - Morais, Daniel Vieira (2019)
For the first time, the anti-hemolytic activity and the enzyme inhibitory activities of Dalbergia ecastaphyllum leaves extracts were tested against α-amylase, α-glucosidase, lipase, acetylcholinesterase, butyrylcholinesterase, tyrosinase and hyaluronidase. The phenolic profile of the obtained extracts was also investigated by high-performance liquid chromatography with photodiode array detection (HPLC-PAD). The extracts showed inhibitory activity against all enzymes evaluated, with the highest inhibitory activity reported for the enzyme hyaluronidase (28.28 ± 2.43 to 72.19 ± 1.40 μg mL-1). The obtained extracts also demonstrate anti-hemolytic activity (52.22 ± 1.62 to 71.17 ± 1.82%). Among the phenolic compounds identified, protocatechuic, vanillic and β-resorcylic acids were the most abundant (1.13 ± 0.06 to 2.53 ± 0.06, 0.90 ± 0.06 to 2.19 ± 0.06 and 1.03 ± 1.62 to 22.11 ± 1.62 mg L-1, respectively). In the statistical analysis, a significant correlation was found between the flavonoids content and all enzymes inhibitory activities. The present study showed that D. ecastaphyllum leaves extracts may have the potential to be used in the therapeutic treatment of several diseases such as Alzheimer, Parkinson, type 2 diabetes mellitus, hyperglycemia, and pigmentation, as well as those associated with oxidative stress.